PERKEMBANGAN PENGERTIAN TINDAK PIDANA KORUPSI DALAM HUKUM POSITIF DI INDONESIA - Pasmatuti, Darda (Ensiklopedia Sosial Review, 2019)
Corruption that occurs in developing countries, because there is abuse of power and authority carried out by officials or state officials. Abuse of power and authority can occur in developing countries, because the understanding of democracy is more interpreted and determined by thinkers in developing countries. Based on Law Number 31 of 1999 concerning Eradication of Corruption Crime which was amended by Law Number 20 Year 2001 concerning Amendment to Law Number 31 Year 1999 concerning Eradication of Corruption Crime, Article 2 and Article 3 defines corruption as follows: Anyone who intentionally violates the law, commits an act enriching himself or another person or a corporation that can harm the state's finance or the country's economy. Every person who aims to benefit himself or another person or a corporation, misusing the authority, opportunity or means available to him because of a position or position that can harm the country's finances or economy. Based on the interpretation of the provisions in the Law, corruption is categorized into two, namely corruption and criminal acts relating to criminal acts of corruption. The first categorization can be seen in the provisions of Article 5-Article 12 of Act Number 20 of 2001 in conjunction with Article 13-Article 16 of Law Number 31 of 1999. The second categorization can be seen in 21-Article 24 of Law Number 31 of 1999.